Reconfigurable pinart to help the blinds visualization - Chaiwat, Kunlapuch; Raksasurasan, Wanchanok; Iamudomchai, Pisit; Intasam, Anongnat; Piyawattanametha, Wibool (My University, 2020)
We developed a reconfigurable pinart model that can transform its topographical surface which is in three-dimension from a stereographic image captured from a webcam. The model relies on a pneumatic pump and solenoid valves to excite each pin stroke via our custom multiplex control system. The travel displacement for each pin stroke is ten centimeters. The reconfiguration time is less than a few minutes with our demonstration reconfigurable pinart prototype of one hundred pixels.
Keywords: Blind; Pinart; Reconfigurable; Visualization